2023
DOI: 10.3846/jcem.2023.18687
|View full text |Cite
|
Sign up to set email alerts
|

Quality Management Platform Inspired During Covid-19 Pandemic for Use by Subcontractors in Private Housing Projects

Abstract: Due to the COVID-19 pandemic in Taiwan, many construction sites must limit the number of people on the jobsite or conduct work independently to avoid the spread of COVID-19. The quality of construction may be in doubt with unclear job handover, especially when workers have COVID-19 infection that should be isolated immediately. On top of that, first-level subcontractor self-inspections are crucial parts of construction process management, and neglecting inspection processes can lead to construction errors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Furthermore, earlier research by de Araujo et al (2017), Martens and Vanchoucke (2018), and Lee & Won (2021) [13][14][15] found additional variables contributing to construction project delays, such as inadequate planning, poor consultant performance, ineffective management, owner-related problems, bureaucracy, and subpar contracts. According to several studies by Korhonen (2020), Liu et al (2022), and Chou et al (2023) [16][17][18], the owner's actions have three main implications for the duration of a construction project: delaying payments to subcontractors, interfering with the contractor's cash flow, and having trouble obtaining the necessary materials. In the meantime, a complicated payment system, missing paperwork, and subpar labor are the main reasons why owners fail to pay their contractors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, earlier research by de Araujo et al (2017), Martens and Vanchoucke (2018), and Lee & Won (2021) [13][14][15] found additional variables contributing to construction project delays, such as inadequate planning, poor consultant performance, ineffective management, owner-related problems, bureaucracy, and subpar contracts. According to several studies by Korhonen (2020), Liu et al (2022), and Chou et al (2023) [16][17][18], the owner's actions have three main implications for the duration of a construction project: delaying payments to subcontractors, interfering with the contractor's cash flow, and having trouble obtaining the necessary materials. In the meantime, a complicated payment system, missing paperwork, and subpar labor are the main reasons why owners fail to pay their contractors.…”
Section: Introductionmentioning
confidence: 99%